2022
DOI: 10.3390/ijerph192114587
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Leisure Activity Post-Stroke: Barriers and Facilitators to Engagement

Abstract: Objectives: To identify barriers and facilitators to engagement when returning to, or participating in, leisure activity post-stroke or Transient Ischemic Attack (TIA). Design: Sequential explanatory, mixed methods study. Setting: 21 hospital sites across England, Wales and Northern Ireland. Participants: Adults with a clinical diagnosis of first/recurrent stroke or TIA. Patients approaching end of life were excluded. Participants were recruited as in-patients or at first clinic appointment and a baseline ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Poststroke fatigue notably affects quality of life and limits individuals’ participation in various daily activities ( 43 ). Research has also indicated that stroke survivors with both reduced physical abilities and fatigue have more difficulties returning to previous leisure activities ( 22 ). Promoting physical activity, particularly aerobic exercise, is a promising treatment for reducing poststroke fatigue ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poststroke fatigue notably affects quality of life and limits individuals’ participation in various daily activities ( 43 ). Research has also indicated that stroke survivors with both reduced physical abilities and fatigue have more difficulties returning to previous leisure activities ( 22 ). Promoting physical activity, particularly aerobic exercise, is a promising treatment for reducing poststroke fatigue ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also limited research exploring which factors are associated with a successful return to daily life for older persons with PSCI. Previous studies investigating factors associated with return to daily life and leisure activities after stroke have shown that cognitive ability, age, and mobility are important factors ( 21 , 22 ). However, most related studies have focused on younger stroke survivors ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…These factors are considered to be associated with an increased risk of vascular cognitive impairment[ 6 ]. Cognitive impairment has a significant impact on the ability to perform daily activities and engage in social life in patients with cerebral infarction, leading to a decrease in quality of life for these patients[ 7 ]. Additionally, cognitive impairment is associated with decreased adherence to treatment and medication, resulting in an impact on treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%